1995
DOI: 10.1037/0022-0167.42.3.279
|View full text |Cite
|
Sign up to set email alerts
|

Progress in resolving problems: A problem-focused style of coping.

Abstract: This investigation reports the development of a multidimensional instrument of stable coping styles that focused on whether one's problem-focused coping efforts were facilitating or inhibiting progress toward resolution of a problem. Study 1 describes the steps in scale construction, including the factor analyses, normative information, and reliability estimates. Study 2 provides initial estimates of the stability of the factor structure and construct, concurrent, and discriminant validity. Study 3 provides ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
197
0
12

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 166 publications
(221 citation statements)
references
References 82 publications
12
197
0
12
Order By: Relevance
“…The SS (6 items) is defined as a tendency to deny problems and avoid coping activities. The RS (5 items) measures a tendency to have strong emotional responses, distortion, impulsivity, and cognitive confusion (Heppner et al, 1995). In the present study, only the SS and RS factors were used.…”
Section: Instrumentsmentioning
confidence: 99%
“…The SS (6 items) is defined as a tendency to deny problems and avoid coping activities. The RS (5 items) measures a tendency to have strong emotional responses, distortion, impulsivity, and cognitive confusion (Heppner et al, 1995). In the present study, only the SS and RS factors were used.…”
Section: Instrumentsmentioning
confidence: 99%
“…The Suppressive Style is a six-item subscale that measures a tendency to deny problems and avoid coping activities. The Reactive Style is a five-item subscale that measures a tendency toward strong emotional responses, distortion, impulsivity, and cognitive confusion (Heppner et al, 1995). Each item uses a 5-point Likert-type scale ranging from 1 (almost never) to 5 (almost all of the time).…”
Section: Measures Attachment (Time 1)mentioning
confidence: 99%
“…We used the Suppressive Style and Reactive Style subscales from the Problem-Focused Style of Coping measure (PF-SOC; Heppner, Cook, Wright, & Johnson, 1995) to assess ineffective coping. The Suppressive Style is a six-item subscale that measures a tendency to deny problems and avoid coping activities.…”
Section: Measures Attachment (Time 1)mentioning
confidence: 99%
“…For these students, suppressive coping may be a temporary solution to avoid hostility and other unpleasant feelings. However, coping literature (Heppner et al, 1995) has indicated negative implications of suppressive coping on psychological outcomes. Thus, the combination of low self-esteem and high use of suppressive coping may enhance the association between perceived discrimination and depressive symptoms relative to the effects of either variable alone.…”
mentioning
confidence: 99%
“…From the dispositional and problem resolution perspective, Heppner, Cook, Wright, and Johnson (1995) developed a coping measure that assessed three styles of coping (i.e., reflective, suppressive, and reactive coping). This is a new way of conceptualizing coping in terms of the outcome of the coping action.…”
mentioning
confidence: 99%